Examining the transplant case composition of early‐career transplant surgeons. Issue 1 (9th November 2022) - Cortez, Alexander R.; Delman, Aaron M.; Quillin, Ralph C.
Abstract: Fellowship training established by the American Society of Transplant Surgeons and certified by the Transplant Accreditation and Certification Council provides trainees with broad exposure and practice readiness for the core aspects of abdominal transplantation. However, the operative case mix of a new transplant surgeon early in practice is unknown. This study examined the volume and composition of the transplant case mix of early‐career transplant surgeons to better inform residents interested in transplantation about potential career opportunities following fellowship. cas 209 early‐career transplant surgeons were identified from the UNOS database containing encrypted surgeon‐specific identifiers and were included in this study. At 5 years into practice, there were 85 (40.7%) kidney‐predominant, 38 (18.2%) liver‐predominant, and 86 (41.1%) multiorgan transplant surgeons. Comparing surgeon subgroups, multiorgan surgeons performed more transplants in year 5 of practice than both liver‐predominant and kidney‐predominant surgeons (both p < .05). This is the first study to describe the transplant case composition of the early‐career transplant surgeons. This data can be used to inform aspiring transplant surgeons about potential career opportunities and to assist fellowship programs in guiding and mentoring fellows.